Journal of Oceanology and Limnology - Yu, Roger Z.; Jenkinson, Ian R.; Xiang, Jianhai; SpringerLink (Online service) (Heidelberg : Science Press : Imprint: Science Press, co-published with Springer.)
Chinese Journal of Oceanology and Limnology (CJOL) aims to disseminate original research articles in the forms of review, research paper, and note. CJOL welcomes high-quality articles on aspects of oceanology (oceanography) and limnology from all over the world, including those in academic coverage: biology (bioinformics, bioengineering), physics (mathematical and computational physics), geology (sedimentology, geophysics, paleontology, geochemistry), chemistry (geochemistry, biochemistry), hydrology, meteorology, and geography; and those in practical coverage: aquaculture, marine resource exploration, remote-sensing, environmental protection, marine engineering, pharmacology, and instrumentation. Manuscripts submitted are considered only on the condition that the contents are not plagiarized nor published elsewhere previously, and must be complied with ethical standards. Articles submitted shall state explicitly the objectives and novelty. The articles shall be written in good English and smooth logic, and well understood by broad audience.
Keywords: Earth sciences; Oceanography; Earth Sciences; Oceanography